Mediation in Marriage Disputes and Divorce (Analytical Study on the Application of Mediation in the Gorontalo Religious Court) - Yasin -; Faradila Hasan; Fikri Amiruddin (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Abstract: This article discussed mediation as a way of resolving marital disputes. Divorce was one form of marital dispute in the Religious Courts, and in terms of resolving marital disputes, mediation was required. Although the rules of mediation in the judiciary are very clear, the facts show that the disputing parties and the courts have not optimized their use so that the divorce rate every year does not experience a significant decrease; on the contrary, it increases. The theory regarding mediation procedures in the Religious Courts has clearly been stated in the Supreme Court of the Republic of Indonesia (No. 1 of 2016). This article aims to analyze the implementation of the mediation process at the Gorontalo Religious Court. Therefore, it is necessary to conduct more in-depth research on the effectiveness of the Gorontalo Religious Court to resolve marital disputes that lead to divorce, which can be avoided, and the litigants can get back together and foster a ‘sakinah mawaddah wa rahmah’ household. This article used a qualitative with an empirical juridical approach. It could be concluded that the mediation had been carried out at the Gorontalo Religious Court under the Regulation of the Supreme Court of the Republic of Indonesia (No. 1 of 2016). Four factors affect successful and unsuccessful mediation, namely the litigation party factor, the mediator factor, the advocate or lawyer factor, and the representative mediation room factor. Abstrak: Artikel ini membahas mengenai mediasi sebagai salah satu cara penyelesaian sengketa perkawinan. Perceraian merupakan salah satu bentuk sengketa perkawinan di Pengadilan Agama dan dalam hal penyelesiaian sengketa perkawinan tersebut maka diperlukan mediasi. Meski aturan mediasi di peradilan sangat jelas, namun fakta menunjukkan bahwa para pihak yang bersengketa dan pengadilan belum mengoptimalkan penggunaannya, sehingga angka perceraian setiap tahun tidak mengalami penurunan yang siknifikan, bahkan sebaliknya meningkat. Teori mengenai prosedur mediasi di Pengadilan Agama secara jelas telah dituangkan Peraturan Mahkamah Agung Republik Indonesia (No. 1 Tahun 2016). Tujuan dari artikel ini adalah untuk menganalisis implementasi proses mediasi di Pengadialan Agama Gorontalo. Oleh karena itu, perlu dilakukan penelitian yang lebih mendalam mengenai Efektifitas Pengadilan Agama Gorontalo dalam upaya penyelesaian sengketa perkara perkawinan yang bermuara pada perceraian dapat dihindari, dan para pihak yang berperkara dapat rukun kembali dan membina rumah tangga yang ‘sakinah mawaddah wa rahmah’. Artikel ini menggunakan metode kualitatif dengan pendekatan yuridis empiris. Dapat disimpulkan bahwa mediasi telah dilakukan di Pengadilan Agama Gorontalo sudah sesuai dengan Peraturan Mahkamah Agung Republik Indonesia (No. 1 Tahun 2016). Faktor mediasi berhasil dan tidak berhasil dapat disebabkan oleh 4 (empat) faktor yaitu faktor pihak berperkara, faktor mediator dan faktor advokat atau pengacara dan faktor ruang mediasi yang representatif. Kata-kata kunci: mediasi, sengketa perkawinan, pengadilan agama Gorontalo